Prevalence of malnutrition risk among institutionalized elderly from North Bohemia is higher than among those in the Capital City of Prague, Czech Republic - Slavíková, Miroslava; Procházka, Bohumír; Dlouhý, Pavel; Anděl, Michal; Rambousková, Jolana (Central European journal of public health, 2018)
OBJECTIVE: The aim of the study is to assess the risk of malnutrition among institutionalized elderly individuals in North Bohemia and compare it to the risk of malnutrition in the capital city of Prague, Czech Republic. In the Czech Republic, very few studies have been conducted with the goal of describing and evaluating the nutritional status of the institutionalized elderly. METHODS: In this study, data was collected from 254 elderly individuals (aged ≥ 65) residing in retirement homes in North Bohemia and then compared with similar data for the elderly living in retirement homes in Prague (the data from Prague were previously published in 2013). The data included an Mini-Nutritional Assessment (MNA) test; anthropometric measurements - Body Mass Index (BMI), waist circumference, triceps skinfold thickness; and biochemical parameters - albumin, prealbumin, transferrin, urea, and creatinine. RESULTS: Mean BMI values were 27.4 kg/m2 for females and 26.3 kg/m2 for males. According to the MNA questionnaire, 10.4% of all tested elderly were malnourished and 50.8% were at risk of malnutrition; lager proportion of females were found to be malnourished than males. Biochemical indicators supported the MNA results. MNA categories correlated positively with independence (r = 0.56; p < 0.001), mental status (r = 0.54; p < 0.001), mobility (r = 0.46; p < 0.001), calf circumference (r = 0.42; p < 0.001), BMI, and the ability to self-feed (both r = 0.37; p < 0.001). The percentage of institutionalized elderly with malnutrition living in North Bohemia and Prague were about the same; however, the percentage of those at risk of malnutrition was higher in North Bohemia (p = 0.006). CONCLUSION: Study results confirmed that the institutionalized elderly face issues that lower their nutritional status and put them at increased risk; clearly these issues need urgent attention.
Keywords: senioři; podvýživa; Prevalence; nutritional status; Malnutrition; senioři nad 80 let; Česká republika; institutionalized elderly; mužské pohlaví; prevalence; Nutrition Assessment; Czech Republic; Homes for the Aged; Geriatric Assessment; Aged, 80 and over; geriatrické hodnocení; ženské pohlaví; hodnocení stavu výživy; Humans; malnutrition; mini-nutritional assessment; domovy pro seniory; Female; Aged; lidé; Male